Colloidal BiF3 nanocrystals: a bottom-up approach to conversion-type Li-ion cathodes. Issue 40 (24th September 2015) - Oszajca, Marek F.; Kravchyk, Kostiantyn V.; Walter, Marc; Krieg, Franziska; Bodnarchuk, Maryna I.; Kovalenko, Maksym V.
Abstract : A facile colloidal synthesis of BiF3 nanocrystals (NCs) via thermal decomposition of bismuth(iii ) trifluoroacetate in oleylamine is reported. Abstract : A facile colloidal synthesis of BiF3 nanocrystals (NCs) via thermal decomposition of bismuth(iii ) trifluoroacetate in oleylamine is reported. The NC size can be tuned from 6 to 40 nm by the adjustment of synthesis parameters. After removal of the capping surfactant molecules, BiF3 NCs were tested as a cathode material for Li-ion batteries. Close to theoretical Li-ion storage capacities of up to 300 mA h g −1 at an average voltage of 3 V were obtained at a current density of 50 mA g −1 .